Different Types of White Matter Hyperintensities in CADASIL - Duchesnay, Edouard; Hadj Selem, Fouad; De Guio, François; Dubois, Mathieu; Mangin, Jean-François; Duering, Marco; Ropele, Stefan; Schmidt, Reinhold; Dichgans, Martin; Chabriat, Hugues; Jouvent, Eric (Frontiers in Neurology, 2018)
1.1 Objective In CADASIL (Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy), white matter hyperintensities (WMH) are considered to result from hypoperfusion. We hypothesized that in fact the burden of WMH results from the combination of several regional populations of WMH with different mechanisms and clinical consequences. 1.2 Methods To identify regional WMH populations, we used a 4-step approach. First, we used an unsupervised principal component algorithm to determine, without a priori knowledge, the main sources of variation of the global spatial pattern of WMH. Thereafter, to determine whether these sources are likely to include relevant information regarding regional populations of WMH, we tested their relationships with: 1) MRI markers of the disease; 2) the clinical severity assessed by the Mattis Dementia Rating scale (cognitive outcome) and the modified Rankin's score (disability outcome). Finally, through careful interpretation of all the results, we tried to identify different regional populations of WMH. 1.3 Results The unsupervised principal component algorithm identified 3 main sources of variation of the global spatial pattern of WMH, which showed significant and sometime inverse relationships with MRI markers and clinical scores. The models predicting clinical severity based on these sources outperformed those evaluating WMH by their volume (Mattis Dementia Rating scale, coefficient of determination of 39.0% vs 35.3%, p=0.01; modified Rankin's score, 43.7% vs 38.1%, p=0.001). By carefully interpreting the visual aspect of these sources as well as their relationships with MRI markers and clinical severity, we found strong arguments supporting the existence of different regional populations of WMH. For instance, in multivariate analyses, larger extents of WMH in anterior temporal poles and superior frontal gyri were associated with better outcomes, while larger extents of WMH in pyramidal tracts were associated with worse outcomes, which could not be explained if WMH in these different areas shared the same mechanisms. 1.4 Conclusion The results of the present study support the hypothesis that the whole extent of WMH results from a combination of different regional populations of WMH, some of which are associated, for yet undetermined reasons, with milder forms of the disease.